A pediatric case of imported dengue hemorrhagic fever in Japan. (27th June 2017) - Kusama, Yoshiki; Ito, Ken; Tajima, Shigeru; Kutsuna, Satoshi
Abstract: We report a case of imported dengue hemorrhagic fever (DHF) in a 10‐year‐old Philippine boy. The patient was admitted to the hospital with a 4‐day history of high fever, headache, and malaise, and a 2‐day history of epistaxis and hematemesis. Symptoms deteriorated after admission, and the patient was subsequently diagnosed with DHF. DHF occurs more frequently among cases of reinfection than among cases of primary infection. Therefore, physicians should recognize the difference in the risk of developing DHF between patients in endemic and nonendemic areas.